The Determinants of Cyprus Banks’ Risk-Taking Behaviour and how they have been affected by the 2008 Global Financial Crisis: An Empirical Investigation. - Pavlidou, Anna (2012)
The past decade was full of changes for the third largest Mediterranean island, Cyprus. The entrance in the European Union and the adoption of Euro have brought significant changes in the Cyprus economy. The remarkable rise of the Cypriot economy until 2008 and the sudden recent failure of its banking system have made Cyprus a very interesting country to study. The purpose of this paper is to investigate and determine the factors that affect the risk-taking behaviour of Cyprus banks and whether the 2008 Global financial crisis and the subsequent European sovereign debt crisis, have affected in any way these determinants. The analysis is conducted on a sample of 18 banks for the period of 2005 to 2011. The results show evidence that the risk-taking behaviour of Cypriot banks was significantly affected as a result of the crisis leading to a decrease in the banks’ lending activities. Even though credit crisis turned to be insignificant, capital adequacy seems to play an important role especially in the post-crisis period.